Use of enantiomerically pure 7-azabicyclo[2.2.1]heptan-2-ol as a chiral template for the synthesis of aminocyclitols - Pandey, Ganesh; Tiwari, Keshri Nath; Puranik, Vedavati G. (Organic Letters, 2008)
Using enantiopure 7-azabicyclo[2.2.1]heptane-2-ol, the synthesis of cis- as well as trans-2-aminocyclohexanols, dihydroconduramine E-1, and ent-conduramine F-1 has been described.